Physics-chemical study of hydration process of three calcium aluminate phase and Metakaolin - Erdenebat, Ts; Sanjaasuren, R (Mongolian Journal of Chemistry, 2014)
This research based on X-Ray Diffraction, SEM and chemical analyses were revealed that decreasing of Ca(OH)2 phase content and increasing of C3AH6 and trisulfate aluminate calcium-3 as the stable phases for the hydration period of first 30 to 60 minutes when comparing K-crent doping to the phase to without any doping. Also results have been proposed in case of doping metakaoline to draw structural analogies as formation of stable hydrated phases and the decrease of new formed unstable crystalline metaphases in the early stage of 3CAO·Al2O3 hydration process. DOI: http://dx.doi.org/10.5564/mjc.v12i0.183 Mongolian Journal of Chemistry Vol.12 2011: 107-112